A systematic review of the potential effects of medications and drugs of abuse on dopamine transporter imaging using [123I]I-FP-CIT SPECT in routine practice. - Chahid, Youssef; Sheikh, Zulfiqar H.; Mitropoulos, Max; Booij, Jan (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose: In routine practice, dopamine transporter (DAT) imaging is frequently used as a diagnostic tool to support the diagnosis of Parkinson's disease or dementia with Lewy bodies. In 2008, we published a review on which medications and drugs of abuse may influence striatal [123I]I-FP-CIT binding and consequently may influence the visual read of an [123I]I-FP-CIT SPECT scan. We made recommendations on which drugs should be withdrawn before performing DAT imaging in routine practice. Here, we provide an update of the original work based on published research since 2008. Methods: We performed a systematic review of literature without language restriction from January 2008 until November 2022 to evaluate the possible effects of medications and drugs of abuse, including the use of tobacco and alcohol, on striatal DAT binding in humans. Results: The systematic literature search identified 838 unique publications, of which 44 clinical studies were selected. Using this approach, we found additional evidence to support our original recommendations as well as some new findings on potential effect of other medications on striatal DAT binding. Consequently, we updated the list of medications and drugs of abuse that may influence the visual read of [123I]I-FP-CIT SPECT scans in routine clinical practice. Conclusion: We expect that a timely withdrawal of these medications and drugs of abuse before DAT imaging may reduce the incidence of false-positive reporting. Nevertheless, the decision to withdraw any medication must be made by the specialist in charge of the patient's care and considering the pros and cons of doing so.